Heart Rate Recovery Changes during Competition Period in High-Level Basketball Players (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. Replete schedule of competitions and intense training are features of contemporary team sports. Athletes, especially the most involved ones, may not have enough time to recover. As a consequence, aggregated fatigue can manifest in some undesirable form and affect athlete’s performance and health.Research aim. The aim of this study was to evaluate the changes in heart rate recovery (HRR) and investigate possible relations with sport-speciﬁ c measures of efﬁ cacy in professional basketball players during competition season.Research methods. Eight male high-level basketball players (mean ± SD, body mass, 97.3 ± 11.33 kg; height 2.02 ± 0.067 m, and age 23 ± 3.12 years) were investigated. The same basketball speciﬁ c exercise was replicated several times from September till April during the practice sessions in order to assess the personal trends of HRR. Heart rate monitoring was performed using POLAR TEAM SYSTEM. Investigated athletes were ranked retrospectively according to the total amount of minutes played and the coefﬁ cients of efﬁ cacy. Research results. There were signiﬁ cant differences in the trends of HRR between the investigated players. The most effective players showed decreasing trends of HRR in all cases of ranking.Discussion and conclusions. Research ﬁ ndings have shown that the quality of heart rate recovery differs between basketball players of the same team and could be associated with sport-speciﬁ c efﬁ cacy and competition playing time.Keywords: adaptation, autonomic control, monitoring training.